Penerapan Model Bisnis Canvas dalam Mengembangkan Bisnis UMKM Madu Yasa 22 Kota Madiun - Firdiana Nur Auliya; Sonja Andarini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Honey is a sweet liquid produced by honey bees from the nectar of flowers. Honey is a herbal product that has been used for centuries for health and culinary benefits. It has been believed by Indonesian people since ancient times for its usefulness because it is made of natural ingredients and has no side effects. One of these herbal companies is UMKM Madu Yasa 22 Madiun. Honey is also considered a good sugar substitute that can be consumed for your culinary needs. The emergence of similar industries has created tight competition which has resulted in sharp turnover fluctuations. Therefore, UMKM Hadu Yasa 22 needs a new strategy to formulate the right business model as well as develop and address these challenges. This research aims to analyze the UMKM Honey Yasa 22 model using a business model canvas approach and evaluate it based on SWOT analysis to produce recommendations for improvement of the business model block element. The research uses a qualitative descriptive approach using Business Model Canvas (BMC) data analysis techniques and SWOT analysis that includes the use of IFAS and EFAS. Data collection methods are interviews with selected informants and document research. The research informants consisted of the owners, employees, and customers of UMKM Madu Yasa 22 randomly selected, a total of 11 people who have made repeated purchases. The findings indicate that SWOT analysis diagrams lead to diversification strategies (product/market) that serve as input for business improvement of canvas models. From its implementation, it recommended improvements to nine elements of Canvas Business Model, as well as strategies that enable the development of UMKM Madhu Yasa 22 business.